Prototype of Monitoring and Control System of SCADA-based Water Tank Level - Irvawansyah Irvawansyah; Abdul Azis Rahmansyah (P3M Politeknik Negeri Indramayu, 2018)
The monitoring and water level controlling system is one sample of the simple industrial automation. Monitoring and controlling SCADA based water level can make it easier to do observation and controlling real time. This research have to design system water level control using ultrasonic sensors and equipped with display interface on laptop. This research is an R&D research that starts from the phase of problem identification, desing, and testing. Test results show good performance in accordance with the desired, where the water pump can be turned on when the water level at the reservoir reaches 10 cm and will be stopped automatically if the water level in tank reaches 70 cm. Monitoring and controlling water level can be done in real time on the laptop interface. So this system can be used as an alternative SCADA learning Media.